A new research trend in social neuroscience: Towards an interactive‐brain neuroscience. Issue 3 (2nd April 2014) - Liu, Tao; Pelowski, Matthew
Abstract The ability to flexibly modulate our behaviors in social contexts and to successfully interact with other persons is a fundamental, but pivotal, requirement for human survival. Although previous social neuroscience research with single individuals has contributed greatly to our understanding of the basic mechanisms underlying social perception and social emotions, much of the dynamic nature of interactions between persons remains beyond the reach of single‐brain studies. This has led to a growing argument for a shift to the simultaneous measurement of the brain activity of two or more individuals in realistic social interactions—an approach termed "hyperscanning." Although this approach offers important promise in unlocking the brain's role in truly social situations, there are multiple procedural and theoretical questions that require review and analysis. In this paper we discuss this research trend from four aspects: hyperscanning apparatus, experimental task, quantification method, and theoretical interpretation. We also give four suggestions for future research: (a) electroencephalography and near‐infrared spectroscopy are useful tools by which to explore the interactive brain in more ecological settings; (b) games are an appropriate method to simulate daily life interactions; (c) transfer entropy may be an important method by which to quantify directed exchange of information between brains; and (d) more explanation is needed of the results of interbrain synchronization itself.